IMPLEMENTASI KEMITRAAN KEHUTANAN DI KESATUAN PENGELOLAAN HUTAN PRODUKSI WAY TERUSAN - Yuni Ayu Wandira; Hari Kaskoyo; Indra Gumay Febryano; Slamet Budi Yuwono (Jurnal Hutan Tropis, 2020)
One of the government policies to increase community participation in forest management is Forestry Partnership.  The purpose of this study was to determines the process of forestry partnership implementation in KPHP Way Terusan.  Data collection used in this research was interviews and then the data is analyzed descriptively. The results showed that the implementation process of forestry partnership was long enough and have a lot of challenges.  The supporting factors in forestry partnership were the existence of high support done by the community towards forestry partnership programs, communities high trust to KPHP Way Terusan and high support by other related parties (stakeholders).  Inhibit factors in forestry partnership were low capabilities of human resources, the problems within farmer groups organization, maintainless communications between government and farmer groups and low community participation.